ANTECEDENT TERHADAP KEPATUHAN WAJIB PAJAK BADAN DENGAN TAX AMNESTY SEBAGAI PEMODERASI - Dewi, Ayu Komala; Djadang, Syahril; Darmansyah, Darmansyah (Universitas Pakuan, 2017)
ABSTRACTThis study aims to identify and analyze the impact of tax audit and enforcement of compliance on corporate tax payers, with the tax amnesty as a moderating factor. The study population was registered corporate tax payers in KPP Pratama Depok. This research is using random sampling method with a total of 100 respondents. Data analysis was performed using Moderate Regression Analyst (MRA), which contains elements of interaction (multiplication of two or more independent multiplication) by using SPSS 22 for windows. The study used a questionnaire statement that is processed with statistical test. The results showed that the tax audit, law enforcement if it is moderated by tax amnesty has positively significant impact on tax compliance entities. Â Keywords: Tax Audit, Enforcement, Tax Amnesty, Tax Payer Compliance